Comparison of Postoperative Pain Following One-Visit and Two-Visit Vital Pulpectomy in Primary Teeth: A Single-Blind Randomized Clinical Trial - Farokh-Gisour, Elham; Parirokh, Masoud; Kheirmand Parizi, Marjan; Nakhaee, Nouzar; Aminizadeh, Masumeh (Iranian Endodontic Journal, 2019)
Introduction: The aim of this study was to compare post-operative pain following one-visit pulpectomy and placing stainless steel crown (SSC), with two-visit treatment (performing pulpectomy at the first visit followed by placing SSC at the next visit one week later) in vital pulp of primary molars with carious involvement. Methods and Materials: In this randomized clinical trial, 100 children aged 6-12 years with a carious primary molar tooth in need of pulpectomy were randomly divided into two groups of 50 each. In one-visit group, pulpectomy and placement of SSC were carried out at the same appointment. In two-visit group, pulpectomy of root canals was carried out at the first visit and placement of SSC was performed at the second visit one week after the first appointment. Post-operative pain was recorded using visual analogue scale (VAS) during one week after each treatment visit. Results: No significant difference was found in the mean age and gender distribution between the two groups (P˃0.05 for both comparisons). Findings revealed that in the two-visit (pulpectomy) group during first three days and 4-7 days after the first treatment appointment, pain felt by the children was significantly lower than that felt by the one-visit group at the same time period (P˂0.0001 for both comparisons). Moreover, children in two-visit (pulpectomy) group consumed significantly lower amount of analgesics than those in the one-visit group (P<0.0001). Conclusion: No significant difference was found between pain felt by children during the first three days following one-visit pulpectomy and placement of SSC at the same appointment. Therefore, one-visit treatment of vital primary tooth is recommended. Keywords: Children; One-Visit; Pain; Postoperative; Primary Teeth; Pulpectomy; Two-Visit